2014
DOI: 10.1007/s00125-014-3373-y
|View full text |Cite
|
Sign up to set email alerts
|

A vascular mechanism for high-sodium-induced insulin resistance in rats

Abstract: Aims/hypothesis High sodium (HS) effects on hypertension are well established. Recent evidence implicates a relationship between HS intake and insulin resistance, even in the absence of hypertension. The aim of the current study was to determine whether loss of the vascular actions of insulin may be the driving factor linking HS intake to insulin resistance. Methods Sprague Dawley rats were fed a control (0.31% wt/wt NaCl) or HS (8.00% wt/wt NaCl) diet for 4 weeks and subjected to euglycaemic-hyperinsulinaemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 50 publications
(94 reference statements)
3
41
1
Order By: Relevance
“…It is important to note that most animal models used to investigate insulin resistance develop both myocyte and microvascular insulin resistance. However, we and others have evidence demonstrating that the microvasculature can become insulin resistant prior to changes in myocyte insulin sensitivity suggesting the vasculature is an early contributor to development of insulin resistance …”
Section: Microvascular‐induced Muscle Insulin Resistancementioning
confidence: 72%
See 2 more Smart Citations
“…It is important to note that most animal models used to investigate insulin resistance develop both myocyte and microvascular insulin resistance. However, we and others have evidence demonstrating that the microvasculature can become insulin resistant prior to changes in myocyte insulin sensitivity suggesting the vasculature is an early contributor to development of insulin resistance …”
Section: Microvascular‐induced Muscle Insulin Resistancementioning
confidence: 72%
“…We have recently characterised two dietary animal models that develop microvascular insulin resistance . In the first model dietary fat in rats is moderately increased from 5% to 9% wt./wt., rather than the more common 5‐ to 7‐fold increase employed in many studies .…”
Section: Microvascular‐induced Muscle Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…An insulin decrease has also been observed with HSD-fed Wistar rats [26,51]. HSD-induced insulin resistance (IR) was found to be driven by impaired microvascular responsiveness to insulin [52] and linked with decreased insulin sensitivity, phosphatidylinositol (PI) 3-kinase or Akt activation [53], and AT hypoxia [54]. Further study indicated that HSD and IR, alone or combined, might have a strong relationship with obesity-related metabolic disorders [55].…”
Section: Hsd and Gi Hormonesmentioning
confidence: 94%
“…In our laboratory we have recently characterised two dietary animal models of insulin resistance (Premilovac et al . , ). Both of these models support the concept that microvascular insulin resistance develops before, and contributes to, reduced muscle glucose uptake in vivo .…”
Section: Introductionmentioning
confidence: 99%